2010
DOI: 10.3109/00207451003760080
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Alzheimer's Disease: An Understanding of Pathology and Therapeutic Avenues

Abstract: Alzheimer's disease is a neurodegenerative disorder with unclear etiology for a few decades. Many animal models employed to study the etiology of the disease and test the efficacy of a drug could give limited understanding of these events. Introduction of aluminum salts into aged New Zealand rabbit brain could demonstrate neurofibrillary tangle formation in 1965. This outstanding contribution substantiated the role of aluminum in Alzheimer's disease in turn becoming the basis further molecular studies in rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…AD being a deleterious neurodegenerative disorder in the elderly reposes a robust threat to the developed nations with burgeoning patients and annual costs on health care system [1,2]. Its etiology entails oxidative stress, deposition of extracellular amyloid beta (Ab) plaques, formation of intracellular neurofibrillary tangles (NFTs), metal mediated neurotoxicity, mutations in genes, neuroinflammation, hyperphosphorylation of tau and apoptosis [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…AD being a deleterious neurodegenerative disorder in the elderly reposes a robust threat to the developed nations with burgeoning patients and annual costs on health care system [1,2]. Its etiology entails oxidative stress, deposition of extracellular amyloid beta (Ab) plaques, formation of intracellular neurofibrillary tangles (NFTs), metal mediated neurotoxicity, mutations in genes, neuroinflammation, hyperphosphorylation of tau and apoptosis [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular deposition of beta amyloid, intracellular NFT formation and oxidative stress induced by impaired metabolic pathways and metals are the hallmarks of AD [1][2][3][4][5]. Wealth of studies showed more than 4 decades ago that microtubule-based axonal transport and synaptic function might be impaired in AD [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since the H1R has been recently implicated in hippocampal neurogenesis (Ambree et al, 2014), it would be interesting to examine whether the application of histamine-related agents (including the histamine precursor Lhistidine) would enhance adult neurogenesis in animal models of Alzheimer's disease that exhibit hippocampal neurodegeneration (Cavanaugh et al, 2014;Duff, 1997;Kitazawa et al, 2012;Marlatt et al, 2010;Obulesu et al, 2010).…”
Section: Histamine-related Mouse Mutants and Dementia-like Behavioralmentioning
confidence: 99%